Indirect lmunofluorescent Antibody Test for Detecting Chlamydial Infection - AL- Kaysi, A. M (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
A total of 243 serum samples were tested for the presence of Chlamydia antibodies by ind irect immunofluorescent antibody test.Ninety nine females were suffering from abortions, 64 were infertile and other 80 were none aborted women. The incidence of Ch lamydia were (15%, 9.4%) and (3.8%) in abortion, infertile and non aborted group, respecti vely. The results also showed a difference in prevalence rate between the age groups. The highest incidence was found in the age group 20-39 years. Levels of inununolobu lines (1gG, JgM) were also detenn i ned to identify a high positi ve titer of these chosen samples.